Policy Discourse on Electric Mobility in Nepal (Southwestern Research Journal, 2023)
In recent years, electric vehicles have become an increasingly appealing alternative due to rising fuel prices and commitment of governments from all over the world to reduce pollution and global greenhouse gas emissions. This paper intends to explore the complex network of existing policy barriers that governments at all levels must overcome in order to develop a sustainable and long-term e-mobility strategy. The study not only examines the existing gaps but also uncovers the shortcomings in policies enacted by state and provincial governments of Nepal to promote electric mobility in the country. A lack of top-level commitment, policy coherence issues, and undefined targets for addressing EV challenges are discussed in the paper. Furthermore, this research brings in a global perspective by showcasing impressive instances from nearby countries and world leaders in this field. This analysis may offer valuable insights for policymakers aiming to enhance existing policy gaps.